1984
DOI: 10.1103/physrevc.29.2377
|View full text |Cite
|
Sign up to set email alerts
|

Approximation for nuclear densities to be used in multiple scattering problems

Abstract: We have investigated the possibility of describing nuclear one-body densities as a sum of step functions.The results show that a relatively limited number of bins is sufficient to fit the form factor up to 2-3 fm . Such approximate nuclear densities are useful to calculate various contributions in multiple scattering problems; two examples are presented.In the multiple scattering description of nuclear reactions at intermediate energies, situations often occur in which second and higher order corrections have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The potential V ( r , 0 ) is then introduced in a Schrodringer-type equation where w = (p'+ m2)2 is the total energy in the CM system. The particular choice made for f ( q ) (equation (3)) gives rise to a potential which has a spin-independent and a spin-orbit part. For proton scattering on a spin-zero nucleus; the corresponding scattering amplitude has two components, as is well known F ( q ) = F , ( q ) + m.fiF,(q).…”
Section: Optical Potential and Wave Equationmentioning
confidence: 99%
See 3 more Smart Citations
“…The potential V ( r , 0 ) is then introduced in a Schrodringer-type equation where w = (p'+ m2)2 is the total energy in the CM system. The particular choice made for f ( q ) (equation (3)) gives rise to a potential which has a spin-independent and a spin-orbit part. For proton scattering on a spin-zero nucleus; the corresponding scattering amplitude has two components, as is well known F ( q ) = F , ( q ) + m.fiF,(q).…”
Section: Optical Potential and Wave Equationmentioning
confidence: 99%
“…%b ko In order to deal with a semi-realistic example, the parameter values were chosen in a way to simulate proton-'He elastic scattering at 1 GeV incident energy [3].…”
Section: V(0 Y)= -A---and *2c 'Lab (2) A(0)mentioning
confidence: 99%
See 2 more Smart Citations
“…Franco and Yin [31] had earlier introduced the phase factor exp − γ nn q 2 2 in f NN (q) by defining a nn = β nn + iγ nn . Studies show that by treating γ nn as a free parameter, good agreement between theoretical and experimental cross sections could be achieved [31][32][33]. Recently, considering three different models for the interaction potential, Dedonder et al [34] have shown that the phase of the scattering amplitude is a sensitive function of the relative size of the radii of the real and imaginary parts of potential.…”
Section: Introductionmentioning
confidence: 99%